Financial reforms, financial development, and economic growth in the Ivory Coast - Vassik Sanogo; Richard K. Moussa (Economies, 2017)
This study investigates the relationship between financial development and economic growth in the Ivory Coast over the period from 1961 to 2014. The final goal of this research is to develop a procedure to identify the effects of financial reforms for the Ivory Coast economic growth. Therefore, to achieve this goal, we first conducted a common component analysis (CCA) on our time series data to create: (1) a variable that would be the most appropriate proxy for the financial development; and (2) a vector of control variables for economic growth. Second, a vector autoregression model (VAR) with restriction was used as an appropriate specification of the dynamic relationship between the proxy of financial development, economic growth and other important factors of that growth (vector of control variables). Results suggest that in the Ivory Coast, growth in financial development is synonymous with the overall economic growth of the national economy. This study addresses the controversy over the appropriate proxy for the financial development in the Ivory Coast and it establishes a causal relationship between the financial development and the national economic growth.
Keywords: B41; C32; E63; G28; O16; O47; 330; financial development; economic growth; vector autoregression model; common component analysis; causality; Ivory Coast